2003
DOI: 10.1007/s00134-002-1619-5
|View full text |Cite
|
Sign up to set email alerts
|

Temperature measurement in intensive care patients: comparison of urinary bladder, oesophageal, rectal, axillary, and inguinal methods versus pulmonary artery core method

Abstract: In critically ill patients, urinary bladder and oesophageal electronic thermometers are more reliable than the electronic rectal thermometer which is better than inguinal and axillary gallium-in-glass thermometers to measure core temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
155
0
11

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(174 citation statements)
references
References 22 publications
8
155
0
11
Order By: Relevance
“…Furthermore, several studies have shown that even more invasive core thermometry methods (e.g., rectal or bladder thermometry) perform outside of the B 0.5°C limits of agreement range. 26,27 Our results are consistent with our previous research using a non-disposable sensor in intensive care patients as well as patients undergoing abdominal surgery. 11 Despite the fact that forehead temperatures are usually slightly lower in the regional anesthesia patients, the performance of the double-sensor in these patients was comparable with its performance in patients undergoing general anesthesia.…”
Section: -3supporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, several studies have shown that even more invasive core thermometry methods (e.g., rectal or bladder thermometry) perform outside of the B 0.5°C limits of agreement range. 26,27 Our results are consistent with our previous research using a non-disposable sensor in intensive care patients as well as patients undergoing abdominal surgery. 11 Despite the fact that forehead temperatures are usually slightly lower in the regional anesthesia patients, the performance of the double-sensor in these patients was comparable with its performance in patients undergoing general anesthesia.…”
Section: -3supporting
confidence: 92%
“…Since bladder and esophageal temperature are highly correlated, we consider it acceptable to compare the two groups. 27 In conclusion, the latest generation of the Draeger doublesensor thermometer was sufficiently accurate and comparable in patients undergoing general and regional anesthesia. We thus suggest that this sensor can replace the esophageal or other invasive temperature probes in patient populations where placement of invasive probes is not possible.…”
Section: -3mentioning
confidence: 80%
“…Cork et al [19] suggest that bladder temperature is as accurate a source for core temperature measurement as the esophagus, rectum, larynx, or the tympanic membrane. Lefrant et al [20] have…”
Section: Discussionmentioning
confidence: 98%
“…Tympanic, nasopharyngeal and rectal probes are useable, but the bladder, oesophagus or blood (pulmonary artery or Picco catheter) are most frequently used for temperature control during MTH maintenance. 55 Recommendation: We recommend that a rapid, efficient and safe cooling strategy be used (GOR D). There are no specific methods for MTH that can be recommended.…”
Section: Methods For Mthmentioning
confidence: 99%